Assessment of double haploid culture conditions in bell pepper (Capsicum annuum L.) - Bhattacharya, Anjanabha; Palan, Bhavesh; Mali, Kishor; Char, Bharat (The Indian Journal of Genetics and Plant Breeding, 2016)
The present study was performed to generate double haploid lines in bell pepper with high regeneration efficiency via anther culture. In total, 825 anthers were plated on five different modified MS media viz., MS I, MS II, MS III, MS IV and MS V. The number of embryoids formed was found to be highest on MS IV media (26 embryoids) as compared to others. Forty five embryoids were developed on five media combinations, out of which 19 were regenerated into plantlets. Therefore, the optimized media i.e. MS IV in this study may be suitable for the development of double haploid lines in other economically important bell pepper as well as hot pepper genotypes through anther culture.